2016
DOI: 10.1186/s12889-016-3387-0
|View full text |Cite
|
Sign up to set email alerts
|

Trends in major risk factors and mortality from main non-communicable diseases in Lithuania, 1985–2013

Abstract: BackgroundThis study aimed to assess the trends in the prevalence and levels of risk factors and mortality from main non-communicable diseases in the Lithuanian population aged 45–64 years during 1985 to 2013.MethodsData from four general population surveys conducted between 1985 and 2008 were used. All these surveys were carried out in Kaunas city and five randomly selected municipalities of Lithuania. Risk factors measured at each survey included regular smoking, overweight, obesity, arterial hypertension, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 40 publications
0
13
1
1
Order By: Relevance
“…methods originally developed by the WHO MONICA Project [13]. Similar longitudinal population data have been-to our knowledge-available only in Sweden [14], Lithuania [16] and Finland [15]. Continuous favorable changes in smoking habits in males, an overall significant decrease in BP and total cholesterol values, as well as a rise in the awareness, treatment and control of hypertension in both genders were found.…”
Section: Plos Onementioning
confidence: 87%
“…methods originally developed by the WHO MONICA Project [13]. Similar longitudinal population data have been-to our knowledge-available only in Sweden [14], Lithuania [16] and Finland [15]. Continuous favorable changes in smoking habits in males, an overall significant decrease in BP and total cholesterol values, as well as a rise in the awareness, treatment and control of hypertension in both genders were found.…”
Section: Plos Onementioning
confidence: 87%
“…In our study, we found that proportions of women who survived 1 and 5 years after the stroke were significantly higher than in men. This may be due to the fact that the prevalence of harmful lifestyle risk factors in Lithuanian men is significantly higher than in women [31]. Men are less likely to control their blood pressure effectively, and among men other chronic non-communicable diseases such as ischemic heart disease, DM, which can increase the chance of death, are diagnosed more frequently [9, 32].…”
Section: Discussionmentioning
confidence: 99%
“…In Lithuania for example, smoking prevalence increased 1985–2013 in both sexes, as well as hypertension and obesity, which contributed to a slowing decline in CVD mortality. 114 …”
Section: Disparities In the Declining Cvd Mortality Trendsmentioning
confidence: 99%